HS-SPME-GC-MS detection of volatile compounds in Myrciaria jabuticaba Fruit - Rondán, Gerby (2018)
This study was performed to investigate the volatile compounds for the characteristic aroma in jabuticaba fruit distributed in southern and central regions of Brazil. The present work combines headspace solid phase microextraction (HS-SPME) and high resolution gas chromatography-mass spectrometry (GC-MS) techniques to identify and quantify the volatile compounds. The influence of different SPME fibers (CAR/PDMS and DVB/CAR/PDMS) in extraction of volatile compounds was evaluated. The effects of extraction temperature and salt concentration (NaCl) in the extraction medium were studied using the response surface methodology in order to achieve the highest extraction efficiency. The better extraction of volatile compounds was achieved by using a CAR/PDMS fiber and the optimum adsorption conditions were at 42 °C for 30 min and 5% NaCl concentration. A total of 71 compounds were identified, among these, 57% were terpenes which was the most representative class of compounds, followed by esters (19%), aldehydes (10%), alcohols (5.5%) and aromatics compounds (4.4%) and other organic compounds 2.8%. Limonene and ethyl acetate were the volatile compounds that showed highest relative concentration and these could contribute to the characteristic aroma of the jabuticaba fruit along with other compounds such as b-pinene, δ-cadinene, linalool, b-guaiene, and α-caryophyllene.